ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN INFORMATICS EDUCATION METHODOLOGICAL BASIS - Ilyasova, Z.K. (SCIENCE and SOCIETY, 2026)
This article systematically analyzes the methodological foundations of artificial intelligence (AI) technologies in computer science education. The study examines the impact of AI integration on the individualization, adaptability, and pedagogical effectiveness of the educational process. This article examines how students’ analytical thinking and logical problem-solving skills can be developed using artificial neural networks (ANNs), targeted recommender systems (Recommender Systems), feedback and self-assessment mechanisms, and learning process monitoring capabilities using data analysis.